Model Penentuan Lot Pemesanan Dengan Mempertimbangkan Unit Diskon dan Batasan Kapasitas Gudang dengan Program Dinamis - Dana Marsetiya Utama (Jurnal Teknik Industri, 2017)
The classical model of dynamic programming in determining the economical lot size  of orders generally considers the cost of orders and inventory costs. However, firms are often confronted with the situation of determining the number of economic orders if the seller gives incremental discounts to the buyer and limits the warehouse capacity. In this paper, explains the model of determining lot order by considering discount and limitation of warehouse capacity with dynamic program. The dynamic program model is compared with the Economic Order Quantity (EOQ) model considering the discount and the limitation of warehouse capacity. The comparison result shows that dynamic programming model can minimize total inventory cost compared to EOQ.